(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: This study aims to investigate the effects of yttrium oxide (Y2O3) nanopowder inclusion on the mechanical properties, including tear strength, tensile strength, elongation percentage, hardness, and surface roughness, of room temperature-vulcanized maxillofacial silicone elastomers. Materials and Method: Y2O3 nanoparticles (30–45 nm) were added to VST50F platinum silicone elastomers in two weight percentages (1 and 1.5 wt%) as tested by the pilot study that showed superior results. A total of 120 specimens were qualified and divided into the control group and experimental groups (1 and 1.5 wt% Y2O3). Each group was subdivided into four identical subgroups in accordance with intentionally performed tests (tear strength, tensile strength and elongation percentage, shore A hardness, and surface roughness). For each subgroup, 10 specimens were used for each test. Data were statistically analyzed with significance level considered at p < 0.05. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) were also conducted. Results and Discussion: SEM showed that NPs were distributed well within the silicon matrix. FTIR spectra proved no chemical reaction occurred between the Y2O3 NPs and VST50F silicone. Tear strength and hardness values significantly increased in the experimental groups compared with the control group. Tensile strength and surface roughness values increased non significantly. Elongation percentage values decreased non significantly. Conclusion: Incorporating Y2O3 NPs into VST50F maxillofacial silicone improved the tear strength with slight increase in tensile strength. Hardness and surface roughness increased but within accepted clinical levels. Elongation percentage slightly decreased.